Beyond Leadership A Relational Approach to Organizational Theory in Education - Eacott, Scott (Educational Leadership Theory,, 2018)
This book systematically elaborates Scott Eacott's "relational" approach to organizational theory in education. Contributing to the relational trend in the social sciences, it first surveys relational scholarship across disciplines before providing a nuanced articulation of the relational research program and key concepts such as organizing activity, auctors, and spatio-temporal conditions. It also includes critical commentaries on the program from key figures such as Tony Bush, Megan Crawford, Fenwick English, Helen Gunter, Izhar Oplatka, Augusto Riveros, and Dawn Wallin. As such, the text models an approach to, or social epistemology for building knowledge claims in relation rather than through parallel monologues. Eacott's relational approach provides a distinctive, post-Bourdieusian variant of the relational sociological project. Shifting the focus of inquiry from entities (e.g., leaders, organizations) to organizing activity and recognizing how auctors generate - simultaneously emerging from and constitutive of - spatio-temporal conditions unsettles the orthodoxy of organizational theory in educational administration and leadership. By presenting its claims in the context of other approaches, the book stimulates intellectual debate among both relational sociologists and opponents of relational approaches. Beyond Leadership provides significant insights into the organizing of education. As it does not fit neatly into any one field, but instead blends educational administration and leadership, organizational studies, and relational sociology, among others, it charts new territory and promotes important dialogue and debate.